Refining the clinical phenotype associated with missense variants in exons 38 and 39 of KMT2D. Issue 5 (21st January 2022) - Tharreau, Mylène; Garde, Aurore; Marlin, Sandrine; Morel, Godelieve; Ernest, Sylvain; Nambot, Sophie; Duffourd, Yannis; Ternoy, Ninon; Duvillard, Christian; Banka, Siddharth; Philippe, Christophe; Thauvin‐Robinet, Christel; et al.
Abstract: Loss‐of‐function variants in KMT2D are responsible for Kabuki syndrome type 1 (KS1). In the last 5 years, missense variants in exon 38 or 39 in KMT2D have been found in patients exhibiting a new phenotype with multiple malformations and absence of intellectual disability, distinct from KS1. To date, only 16 cases have been reported with classic features of hearing loss, abnormality of the ear, lacrimal duct defects, branchial sinus/neck pits, choanal atresia (CA), athelia, hypo(para)thyroidism, growth delay, and dental anomalies. We report here two families and one unpublished variant, refining the clinical and molecular knowledge on this new entity. Family 1 presented with apparently isolated autosomal dominant choanal atresia, in eight members across three generations. Exome sequencing (ES) in the proband and one cousin revealed a p.Glu3569Gly variant in exon 38 of KMT2D, segregating with choanal atresia in the family. Clinical reevaluation evidenced thyroid dysfunction, mild hearing anomalies, and hypoplastic nipple in some patients. Family 2 presented with nasolacrimal duct obstruction, hearing loss, mild facial features, unilateral axial polydactyly, and unilateral toe V‐VI syndactyly. ES revealed a de novo already reported p.Arg3582Gln variant in exon 38 of KMT2D . Considering these results and the existing literature, we suspect that missense variants in exon 38 of KMT2D are responsible for phenotypes that are even milder (isolated CA) and broader (polydactyly) than what has been previously described.